Maritime Governance Transformation in Riau Islands: Analysis of Policy Implementation and Marine Management Issues - Candra, Mellyana (Kemudi, 2025)
This study aims to analyse the effectiveness of maritime governance policy implementation in the Riau Islands Province (Kepri) in addressing complex maritime challenges. Kepri, which comprises 96% of the maritime territory, holds significant potential as a centre for national maritime management. However, various obstacles—such as limited infrastructure, a shortage of trained human resources, and weak enforcement of maritime law—present substantial challenges in achieving these objectives. This study employs a literature review approach to analyse secondary data from relevant sources, including books, scientific articles, government reports, and policy documents. Drawing on Ehler's (2003) theory regarding the implementation phase, this study evaluates four primary indicators: implementation capacity, law enforcement capacity, conflict resolution, and decision-making at the regional level. The findings indicate that the major challenges faced by the Riau Islands in implementing maritime policies include inadequate infrastructure, limited expertise within the maritime sector, and ineffective coordination among government agencies. Additionally, conflicts between traditional fishermen and large companies, as well as ineffective mechanisms for conflict resolution, further complicate maritime dynamics in the region. A top-down decision-making approach that lacks local community participation also leads to policies that are less responsive to local needs. Based on these findings, the study recommends that the Riau Islands enhance its maritime infrastructure capacity, improve training and human resource development, and foster greater inter-agency collaboration in law enforcement. Furthermore, establishing more transparent and responsive maritime dispute resolution institutions and prioritising inclusive decision-making that engages local community participation is crucial. Synergy between the central government, local governments, and local communities is essential to optimise the management of Kepri's maritime potential.